Higher dietary cost is associated with higher diet quality: a cross-sectional study among selected Malaysian adults - Pondor, Ibnteesam; Gan, Wan Ying; Appannah, Geeta (M D P I AG, 2017)
Food price is a determining factor of food choices; however its relationship with diet quality is unclear in Malaysia. This study aimed to examine socio-economic characteristics and daily dietary cost (DDC) in relation to diet quality in the state of Selangor, Malaysia. Dietary intake was assessed using a Food Frequency Questionnaire (FFQ) and diet quality was estimated using a Malaysian Healthy Eating Index (M-HEI). DDC in Malaysian Ringgit (RM) was calculated from dietary intake and national food prices. Linear regression models were fitted to determine associations between DDC and M-HEI scores and predictors of diet quality. The mean M-HEI score of respondents was 61.31 ± 10.88 and energy adjusted DDC was RM10.71/2000 kcal (USD 2.49). The highest quintile of adjusted DDC had higher M-HEI scores for all respondents (Q1: 57.14 ± 10.07 versus Q5: 63.26 ± 11.54, p = 0.001). There were also positive associations between DDC and M-HEI scores for fruits (p < 0.001) and vegetables (p = 0.017) for all respondents. Predictors of diet quality included carbohydrate (β = 0290; p < 0.001) and fat intakes (β = −0.242; p < 0.001) and energy adjusted DDC (β = 0.196;p < 0.001). Higher dietary cost is associated with healthy eating among Malaysian adults.